How to Boost Spain’s Business Presence in Singapore: Opportunities in the Wake of the Free Trade Agreement with the EU - GARCIA, Maria (Institutional Knowledge at Singapore Management University, 2014)
The recently signed Free Trade Agreement between the EU and Singapore opens up new business opportunities for Spanish companies on the island, which is already Spain’s top trading partner in South-East Asia. One highlight of the accord is the elimination of restrictions on the percentage of foreign investment in financial services and sectors such telecommunications, engineering and shipping. At the same time, the possibility of being able to bid on more government contracts can help companies involved in environmental protection and construction firms. The food industry will benefit from the novel creation of a registry of geographical indications.